Penguatan Pendidikan Karakter Melalui Pelatihan Kitab Al-Akhlak Li Al-Banin Juz I Bagi Para Santri Di Pondok Pesantren - Ahmad Sirfi Fatoni Fatoni; Rahmat Rizal; Achmad Romadin; Muhammad Jamil; Muhammad Rifai (PT. Mediatama Zayna Indonesia, 2026)
This community service programme was prompted by the situation faced by students at the Darul Hasanain Islamic Boarding School in Grogolan, Umbulmartani, Ngemplak, Sleman, Yogyakarta, regarding their limited understanding of ethics, particularly among those in the Ula class. The cultivation of ethical values must be carried out gradually and consistently. Most of them still find it difficult to read Arabic texts and interpret them using Javanese. It is this situation that prompted the volunteers to organise a community service programme, utilising the book “Al-Akhlak li Al-Banin Juz I” by Syekh Umar bin Ahmad Barja’ as the primary reference. The community service method employed comprises two stages: the Preparation Stage and the Implementation Stage. The preparation stage covers several aspects, including: preparation of the community service proposal, preparation of materials, and preparation of training facilities and infrastructure. The implementation stage comprises: an initial introduction to the programme and its rules, the commencement of training, the evaluation stage, and the mentoring stage. The findings indicate that the training on the book “Al-Akhlāq li al-Banīn” Volume I for the students at the Darul Hasanain Islamic boarding school has successfully made a significant contribution to enhancing the students’ skills and knowledge regarding the ethics covered in the book. This is evidenced by the students’ pre-test scores, which initially averaged 67,16; following the post-test, their average score rose to 95,75. Another improvement relates to their behaviour and conduct, which have shown a marked improvement following the delivery of this community service programme.